2021
DOI: 10.1002/admi.202002169
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Activity Enhancement of Surface Hydrides by the Metal–Oxide Interface

Abstract: The observation of hydride species in reduced ceria has triggered recent interest because the formation of hydrides in solid catalysts is limited although hydrides are widely explored in homogeneous catalysis as active species for hydrogenation reactions. Here, a strategy is proposed to enhance the formation and activity of surface hydrides on oxide‐based catalysts via the construction of metal–oxide interface. Specifically, during the reaction with H2, Cu supported on CeO2 nanorods (NRs) is found to enhance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…4b and c). The superior CO 2 methanation reaction on 5Ni/La 2 O 3 might be due to the enhanced H 2 adsorption at the metal-oxide interfaces, 31 We have shown that the oxygen vacancies formed at the metaloxide interface of Ni/La 2 O 3 enhance H 2 adsorption with a strong binding strength, which benefits CO 2 methanation. More importantly, we found the enhanced H 2 adsorption by interfacial oxygen vacancies is ubiquitous for the supported transition metal nanoparticles on La 2 O 3 , not limited to the above-mentioned Ni/La 2 O 3 .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…4b and c). The superior CO 2 methanation reaction on 5Ni/La 2 O 3 might be due to the enhanced H 2 adsorption at the metal-oxide interfaces, 31 We have shown that the oxygen vacancies formed at the metaloxide interface of Ni/La 2 O 3 enhance H 2 adsorption with a strong binding strength, which benefits CO 2 methanation. More importantly, we found the enhanced H 2 adsorption by interfacial oxygen vacancies is ubiquitous for the supported transition metal nanoparticles on La 2 O 3 , not limited to the above-mentioned Ni/La 2 O 3 .…”
Section: Resultsmentioning
confidence: 88%
“…It is worth noting that the hydrogen adsorption favors the formation of lanthanum oxyhydride species at the metal-oxide interfaces. Recently, it has been reported that the surface oxyhydride species could be formed on the reducible CeO 2 during hydrogen adsorption at elevated pressures, [31][32][33][34][35] which brings about a significant effect on the catalytic performance of CeO 2 -supported metal catalysts. 30,36 Here, we also demonstrated that on pure La 2 O 3 surfaces, lanthanum oxyhydride could not be formed due to the non-reducible nature of La 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The silicon–hydride reaction is analogous to the heterolytic cleavage of H 2 on ceria and the formation of surface and bulk hydride species, which are promoted by supported transition-metal catalysts (e.g., Cu, Pd, etc.) and facilitated by the oxygen vacancies of the reduced ceria. Since no H n -T n cage structures are detected, it is apparent that the H–O exchange reaction is able to outcompete the formation of any cage structures with Si–H vertices.…”
Section: Resultsmentioning
confidence: 99%
“…11 Furthermore, Li et al revealed a novel homolytic dissociation process of H 2 to two Ce−H hydride species (2Ce Ov 3+ + H 2 → 2Ce Ov 4+ −H − ) at two Ce 3+ −O v sites on prereduced CeO 2−x powder and thin film, 10 which is kinetically favorable at relative low temperature and leads to the oxidation of Ce 3+ to Ce 4+ as well as the formation of hydrides at oxygen vacancies. 7,12,13 For selective alkyne hydrogenation reactions, it was previously proposed that the immobile surface oxygen atoms on the CeO 2 surface were the active centers, 5,14 where H 2 molecule homolytically dissociates to two reactive OH groups and participates in the dissociative adsorption of alkyne molecule for subsequent hydrogenation, 4,6 whereas O v sites were suggested to be detrimental to both the activity and selectivity of the reaction. However, with the revealing of the important role of oxygen vacancies within ceria for the complex H 2 -ceria interaction, ceria-based catalysts with a proper concentration of O v have also been reported to be beneficial to the reaction.…”
Section: ■ Introductionmentioning
confidence: 99%